Strategy of Strengthening Social Capital of Farmer Group in Agricultural Development - Annas Wibisono, Galih Mukti; Darwanto, Darwanto (Semarang State University, 2016)
In the village, the agricultural development is not certainly oriented to the economic aspect. The social intervention is very important and very helpful for the citizens and the development of the agricultural itself. The purpose of this research is to analyze the social existence, the social influence, and also the systematic strategy that can strengthen the society in developing the agriculture. The method used in this research is the qualitative analysis with phenomenology approach. The qualitative analysis is conducted by the direct observation in the field and in-depth interviews with the respondents that are selected by the purposive sampling. The result shows that a society has formed the farmer organization to have mutual coordination among the members. However, there are some problems that occur on this organization. The values and norms begin to fade and have become the major problem. Another problem is the sense of trust among the citizens and the unoptimal social network utilization. The conclusion is, the Analytic Network Process (ANP) shows that to make a progress of agricultural development, they need to strengthen the social relationship among the citizens to face all the problems that may occur.